Structural Deformation Style and Seismic Potential of the Maoyaba Fault, Southeastern Margin of the Tibet Plateau - Xianbing Zhang; Ning Zhong; Xiao Yu; Guifang Yang; Haibing Li (Remote Sensing)
The southeastern margin of the Tibet Plateau represents one of the most seismically active zones in China and serves as a natural laboratory for investigating the uplift dynamics and lateral expansion mechanisms of the plateau. The Litang fault zone (LTFZ) lies within the northwest Sichuan sub-block on the southeastern margin of the Tibet Plateau, running almost parallel to the Xianshuihe fault zone and forming a V-shaped conjugate structure system with the Batang fault zone (BTFZ). The Maoyaba fault (MYBF) is a significant component of the northwestern part of the LTFZ, exhibiting activity in the late Quaternary. It triggered the ancient Luanshibao landslide and caused the Litang earthquake in 1729 AD, demonstrating intense seismic activity. Employing high-resolution remote sensing interpretation, field surveys, UAV photogrammetry, and UAV LiDAR, this study further examines the geometric distribution and kinematic properties of the MYBF, as well as paleoearthquake events recorded by the fault scarps. Combined with the geometric distribution and kinematic properties of the Hagala fault (HGLF) and Zimeihu fault (ZMHF), this study discusses the late Quaternary structural deformation style and seismic potential of the MYBF. The MYBF could produce earthquakes of approximately Mw 6.7 ± 0.3, with an average co-seismic slip of about 0.68 m and an average recurrence interval of strong earthquakes since the late Quaternary ranging from 0.9 to 1.1 ky. The likelihood of surface rupture earthquakes occurring in the near future is low; however, the expansion of the HGLF could induce moderate to strong earthquakes in the MYB area. The variation in the local tectonic stress field, which is influenced by the Litang–Batang V-shaped structure system and lithological differences, results in the formation of an extensional horsetail structure in the northwestern segment of the LTFZ. Both the HGLF and ZMHF remain active faults. Under the influence of nearly north–south tensile stress, these faults and the Litang–Batang V-shaped structure system collectively regulate the movement of regional crustal material.